Audience sensitivity in chimpanzee display pant hoots. (August 2022) - Soldati, Adrian; Fedurek, Pawel; Dezecache, Guillaume; Call, Josep; Zuberbühler, Klaus
Abstract : Audience effects are key in studies of animal social cognition and are typically investigated during directed social interactions. Male chimpanzees, Pan troglodytes, regularly perform aggressive displays in the presence of others, often targeting a specific group member, and combine this agonistic behaviour with acoustic signals. Here, we were interested in whether the production and structure of pant hoots, a long-distance signal, were influenced by audience composition (i.e. presence and absence of specific individuals). We investigated pant hoots produced during displays by adult and subadult males of Budongo Forest, Uganda. We found that males overall called more often when their preferred social partners and females were absent from the party, as well as when more dominant males were present. We then separately analysed the four phases of pant hoots, introduction, build-up, climax and let-down, and found that audience composition and social context could often explain the presence or absence of each phase. In addition, displays were often accompanied by drumming, especially by older males and when male audiences were small. Our study adds to the growing body of literature on audience effects and other social factors and shows their impact on the structure of a sophisticated vocal sequence, which enhances the communicative capacity in a species with limited vocal control. Highlights: Chimpanzees produce pant hoots, a multiphase vocal utterance, during displays. Audience composition affects individual phase and overall call and production. Patterns of vocal production suggest socially strategical signalling. Chimpanzees selectively withhold different types of information in vocal sequences.